Public Relations Strategies in Disseminating Information through Instagram Social Media in DIY Government - Rahmata, Muhammad Ibnu (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to identify the strategy of the Public Relations Department of the Regional Government of Yogyakarta Special Region in disseminating information through Instagram and to identify the inhibiting and supporting factors in its management. The subjects of this study were the Head of the Public Relations Department of the Regional Government of Yogyakarta Special Region, the administrator of the Regional Government of Yogyakarta Special Region’s social media, and one of its followers on Instagram. The study used a qualitative descriptive approach whose data were compiled through observation, interviews, and documentation. The result showed that in the process of disseminating information through Instagram, the Public Relations Department of the Regional Government of Yogyakarta Special Region applied the following phases: 1) Fact-finding, 2) planning, 3) communication, and 4) evaluation. To manage the Public Relations Department, it applied strategic planning to realize the goal set by the Public Relations Department of the Regional Government of Yogyakarta Special Region itself.